2022
DOI: 10.1111/dth.15672
|View full text |Cite
|
Sign up to set email alerts
|

Adverse outcome and severity of COVID ‐19 in patients with autoimmune bullous diseases: A historical cohort study

Abstract: The ongoing COVID‐19 pandemic has raised concerns regarding the outcome of this infection in patients with autoimmune bullous dermatoses (AIBDs) due to effect of drugs used to treat these disorders. This investigation was performed from the onset of the pandemic to June 1, 2021. Patients with AIBDs who contracted COVID‐19 were evaluated. A generalized linear model was employed to find the predictors of severe COVID‐19 among patients with AIBDs. Ninety‐three patients with AIBDs with a mean age of 50.3 years wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 41 publications
3
24
0
Order By: Relevance
“…Compared with the general population, this systematic review concluded that patients with AIBDs are basically not at increased risk of severe or fatal COVID-19 [ 6 ]. In the later course of the pandemic, five cohort studies focusing on COVID-19 in AIBD patients were published, which mostly confirmed the results of the systematic review [ [7] , [8] , [9] , [10] , [11] ].…”
Section: Risk Of Covid-19 In Aibd Patientssupporting
confidence: 55%
See 3 more Smart Citations
“…Compared with the general population, this systematic review concluded that patients with AIBDs are basically not at increased risk of severe or fatal COVID-19 [ 6 ]. In the later course of the pandemic, five cohort studies focusing on COVID-19 in AIBD patients were published, which mostly confirmed the results of the systematic review [ [7] , [8] , [9] , [10] , [11] ].…”
Section: Risk Of Covid-19 In Aibd Patientssupporting
confidence: 55%
“…Moghadam et al described 93 AIBD patients with COVID-19, out of whom 42 (45.2%) were admitted to the hospital, 11 (26.2%) required intensive care, and 4 (4.3%) died [ 11 ].…”
Section: Risk Of Covid-19 In Aibd Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…facilities and 3 (14%) died. Of note, two studies found that COVID-19 infection and hospitalization rates were higher with prednisolone dosages > 10 mg/die(14,29). In parallel,Kridin et al.…”
mentioning
confidence: 95%